2022
DOI: 10.1155/2022/6499876
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Frequency Information Flows between Global Commodities and Uncertainties: Evidence from COVID‐19 Pandemic

Abstract: Owing to the adverse impact of the COVID-19 pandemic on world economies, it is expected that information flows between commodities and uncertainties have been transformed. Accordingly, the resulting twisted risk among commodities and related uncertainties is presumed to rise during stressed market conditions. Therefore, investors feel pressured to find safe haven investments during the pandemic. For this reason, we model a mixture of asymmetric and non-linear bi-directional causality between global commodities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 90 publications
1
30
0
Order By: Relevance
“…Conversely, Lin and Su [21] found that negative shocks between implied volatility from crude oil and Islamic stocks are more prominent at higher quantiles. Moreover, outcomes generated from the current study do not absolutely deviate from the ones generated by prior studies on conventional assets as well as commodities [5,13,14,18].…”
Section: Preliminary Analysismentioning
confidence: 47%
See 3 more Smart Citations
“…Conversely, Lin and Su [21] found that negative shocks between implied volatility from crude oil and Islamic stocks are more prominent at higher quantiles. Moreover, outcomes generated from the current study do not absolutely deviate from the ones generated by prior studies on conventional assets as well as commodities [5,13,14,18].…”
Section: Preliminary Analysismentioning
confidence: 47%
“…is opens up a gap to further assess the asymmetric effect of implied market volatilities which are forwardlooking. Application of implied volatilities has gained massive attention with conventional stocks [13,14] and cryptocurrencies [15][16][17], as well as commodities [5,18,19]. It is normally found from these studies that negative shocks are mostly transmitted from the implied market volatilities to these assets demonstrating diversification, hedge, or safe haven benefits depending on the market conditions as a result of portfolio formation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since errors could be introduced in the denoised data, upon which the NARDL was applied, further studies may quantify the extent of errors in a decomposed-based empirical investigation to contribute to prior studies [34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%